TRANSFORMASI SISTEM EKONOMI PESANTREN TRADISIONAL IBNUL AMIN - ., Norlaila (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
This paper explores the survavility of Pondok Pesantren Ibnul Amin as the traditional education building. Pesantren Ibnul Amin is the third oldest pesantren pesantren South Borneo that grew as the big traditional pesantren for his quantity of pupil and his popularity in Borneo. Pesantren Ibnul Amin did the traditional education system with the curriculum that refere to Sorogan, Bandongan, and Wetonan method. Even though, Pesantren didnt do the renewing by the adaptation of modern education system, but the Pesantren devoleped the economic and vocational system. This effort made the role of Pesantren Ibnul Amin wider in transforming the Islamic traditional value practically to his students.